Editorial to the Special Issue “Plant Extracts: From Extract Technology to Health Benefits” - Giuseppina Crescente; Stefania Moccia (Foods, 2024)
The valorization of food industry waste is essential to the sustainable development of the agro-food industry, starting from the extraction of plant special metabolites, a challenge that still exists today [...]